Gas holdup in bubble column with suspended low density particles - Yao, Alexander Ka Gue
The fractional gas holdup in an air-water-solid suspension-bubble column was measured for the variable ranges listed below. The column used has an internal diameter of 9.4 cm while the solid particles have a density of 0.948 9/mL.
a. Superficial gas velocity ranges from 0 to 0.37 m/s b. Water flow rate ranges from 0 to 21.1 kg/min which corresponds to a superficial velocity of 0.0507 m/s. c. Fractional solid holdup ranges from 0 to 0.076 for 90 cm column and up to 0.228 for cm column. d. Column height was set at 30, 60 and 90 cm. e. Particulate diameter ranges from 2.98 to 4.17 mm.
Gas holdup was found to increase with increased gas flow and also with increased liquid flow. On the other hand, gas holdup was to decrease with increased column height and also with increased amount of solids. Particle diameter was found to have no significant effect on the gas holdup in the range studied.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Typescript.
Keywords: Gas dynamics; Hydrodynamics